Dimensões do tempo na formação online de educadores - Kuin, Silene (2012)
The thesis is based on the fact that online educator development is established in a fluid time dimension that is determined by the educator s own action of building and dismantling a spatial and temporal reality as s/he connects or disconnects to the virtual environment, which takes place simultaneously with other time dimensions that exist in parallel during their training. The question under investigation emerges from this fact: What are the implications of the simultaneous existence of different time dimensions on the process of online development of education professionals? The research context selected for this study was one of the groups in the School Administration and Technologies Project, a course conducted by PUC/SP for the ETEC and FATEC schools of the Paula Souza Center of the State of São Paulo. The course used a virtual learning environment developed by Microsoft, also partner in this project. The project provided a particularly interesting context for this research question because it included three modalities of interaction: online, centralized face-to-face and decentralized face-to-face. Qualitative methodology was utilized primarily for the collection and interpretation of the data, however, quantitative data was also necessary to measure time allocation of the professionals in training. The study shows the existence of various time dimensions that compete with the time of online education, causing each educator to invest significant amounts of his/her personal time in a course that was conceived essentially as in service. These dimensions were both chronological and psychological, internal and external to the project and to the person. Therefore, the statements of lack of time to dedicate to the course were shown to originate from sources other than an individual incapacity of the participant to administer his/her own time. The professional in training is not isolated, even when apparently alone in the process of online development. His/her time is interrupted by institutional and political time dimensions that cause the educator s institution to be incapable of acting freely and independently of the internal and external interferences from the school environment. The simultaneous existences of these various time dimensions result in work overload and invasion of the professional s free time due to the fact that there are no impervious limits to clearly differentiate between in service training, continuing education and lifelong learning. It is true that lifelong learning has become a part of postmodern reality. However, institutions have taken advantage of this need by appropriating the free time of professionals in training, without assuming the cost of this appropriation